BORDIR KERANCANG DI KOTA PAYAKUMBUH (STUDI KASUS DI CENTONG EMBROIDERY) - Mulyana, Annisa; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The method used is a method of qualitative research .Data collection in thisresearch was conducted using the technique of observation , interview , anddocumentation , which aims to describe about applique kerancang payakumbuh inthe city , includes: motive applique design , a combination of color , the technique, and type of product .Research revealed: 1 applique design motives that many inthe met in embroidery centong naturalist shaped the design of a motive , with thefield of free and filling ornamental patterns .2 in a combination of color and coloruse analog monokromatif is color .3 of the technique make is applique kerancangkerancang directly with embroidery techniques .4 ) type of product appliquekerancang centong embroidery in which there is a parenthesis , kebaya clothes ,tan suit , robe , a pedestal table , bed cover , a shawl , and the veil .Kata kunci: Bordir kerancang, Kota Payakumbuh